THE FACTORS OF STUDENTS’ INVESTMENT IN LEARNING ENGLISH DURING ONLINE LEARNING AT ONE OF SMPN IN MUSI RAWAS - Yenni Anggraini; Eryansyah Eryansyah; Sary Silvhiany (English Review: Journal of English Education, 2023)
Most of the students decided to invest in learning English was because of the perceived capital that provided them with benefits for their academics as well as their future careers. This study used a qualitative narrative inquiry by using interviews and documentation instruments. This study was included the interviewed with seven participants of ninth grader at one of SMPN in Musi Rawas. This study was aimed to investigate the factors affecting the students’ investment in learning English at one of SMPN in Musi Rawas invested in learning English during online learning. The students invested in learning English was because of From the interviews, the results of this study was indicated that: (1) the most dominant  factors affecting the ninth students invested in learning English was family support, the second dominant factor was better English achievement, and the last dominant factor was past experience. This study findings confirmed that the seven students had been put some efforts in their investment in learning English in order to acquire their goals in the present and also future. Then, they also wanted to improve their English language skill. Furthermore, this study may help the students understand about the importance of learning English in the present and also in the future.